Characteristics of progressive supranuclear palsy presenting with corticobasal syndrome: a cortical variant. Issue 2 (February 2014) - Ling, H.; de, R.; Massey, L. A.; Courtney, R.; Hondhamuni, G.; Bajaj, N.; Lowe, J.; Holton, J. L.; Lees, A.; Revesz, T.
<x xml:space="preserve">Abstract</x> Aims Since the first description of the classical presentation of progressive supranuclear palsy (PSP) in 1963, now known as Richardson's syndrome (PSP‐RS), several distinct clinical syndromes have been associated with PSP‐tau pathology. Like other neurodegenerative disorders, the severity and distribution of phosphorylated tau pathology are closely associated with the clinical heterogeneity of PSP variants. PSP with corticobasal syndrome presentation (PSP‐CBS) was reported to have more tau load in the mid‐frontal and inferior‐parietal cortices than in PSP‐RS. However, it is uncertain if differences exist in the distribution of tau pathology in other brain regions or if the overall tau load is increased in the brains of PSP‐CBS. Methods We sought to compare the clinical and pathological features of PSP‐CBS and PSP‐RS including quantitative assessment of tau load in 15 cortical, basal ganglia and cerebellar regions. Results In addition to the similar age of onset and disease duration, we demonstrated that the overall severity of tau pathology was the same between PSP‐CBS and PSP‐RS. We identified that there was a shift of tau burden towards the cortical regions away from the basal ganglia; supporting the notion that PSP‐CBS is a 'cortical' PSP variant. PSP‐CBS also had less severe neuronal loss in the dorsolateral and ventrolateral subregions of the substantia nigra and more severe microglial response in the corticospinal tract than in PSP‐RS; however, neuronal loss in subthalamic nucleus was equally severe in both groups. Conclusions A better understanding of the factors that influence the selective pathological vulnerability in different PSP variants will provide further insights into the neurodegenerative process underlying tauopathies.